Regional trade agreements in the Doha Round: Good for India? - Geethanjali Nataraj (Asian Development Bank Institute (ADBI), 2007)
In recent times, regional trade agreements (RTAs) have become an important factor driving global trade. Though the literature on RTAs continues to grow, few studies highlight the development dimensions of RTAs envisaged in the Doha Development Agenda of the World Trade Organization. In this context, the basic objective of the present paper is to analyze the issues under the Doha Development Agenda with regard to RTAs. Keeping in view this basic objective, this paper highlights some important issues related to rules governing RTAs in order to produce possible suggestions for India's interest. In conclusion the paper recommends stricter rules governing RTAs in the WTO regime and unilateral trade policies as the keys to growth for developing economies like India.
Keywords: F10; F15; O24; 330; Handelsregionalismus; WTO-Regeln; Makroökonomischer Einfluss; Internationale Handelspolitik; Indien